Green Accounting Integrating the Tri Hita Karana Philosophy into Village Economic Development: Akuntansi Hijau Mengintegrasikan Filsafat Tri Hita Karana ke dalam Pengembangan Ekonomi Desa - Putu Adi Suprapto; I Nyoman Abdi; Ida Ayu Putu Sri Astiti Padmawati (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Tourism plays a significant role in Indonesia’s economic growth, particularly through village-based tourism that integrates cultural sustainability and community welfare. Specific background: Tampaksiring Village, designated as a tourism village under Bali Governor Regulation No. 52 of 2021 and Regent Decree No. 762/E-02/HK/2020, possesses rich natural, cultural, and historical assets. However, its development remains suboptimal, revealing a gap between regulatory mandates and actual implementation. Knowledge gap: Existing studies have rarely examined the legal authority and governance challenges of village administrations in optimizing tourism potential within a sustainable development framework. Aims: This study investigates Tampaksiring Village’s authority in managing local tourism and identifies strategies to enhance its tourism potential. Results: Findings show that the village government exercises attribution and delegation authority but struggles to implement integrative and strategic programs. The study highlights five development efforts: branding a unique tourism identity, expanding partnerships, utilizing social media, empowering community participation, and ensuring cultural-environmental sustainability. Novelty: Unlike prior research focusing mainly on promotion, this study underscores the interplay between legal authority, governance, and community-based management as key drivers of sustainable tourism branding. Implications: Strengthening institutional capacity and collaborative governance can transform Tampaksiring into a model of culturally rooted and environmentally responsible tourism development Highlight: Legal authority and governance are crucial for optimizing village tourism. Branding, partnerships, and social media drive tourism visibility. Cultural and environmental sustainability ensure long-term impact. Keywords: Tourism Village, Tampaksiring, Sustainable Development, Governance, Community Empowerment